Anesthesia Management of Space-Occupying Lesion in the Pontine Region due to Brainstem Glioma in a Pediatric Patient: a Case Report - Yustisia, Putu Ngurah Krisna Denta; Sutawan, Ida Bagus Krisna Jaya; Senapathi, Tjokorda Gde Agung; Kurniyanta, I Putu (Syntax Corporation, 2024)
A space-occupying lesion (SOL) in the pontine region of the medulla oblongata, often suspected as a brainstem glioma, poses a complex diagnostic challenge. Brainstem gliomas, primarily diffuse intrinsic, afflict all age groups with a median survival of about 12 months, influenced by tumor characteristics. Comprehensive preoperative evaluation is essential to assess the patient's health status and identify potential complications, guiding optimal anesthesia management. This case report aimed to describe the author's anesthesia technique for managing patients with SOL in the pontine region of the medulla oblongata, focusing on those with suspected brainstem gliomas. A four-year-old girl weighing 20 kilograms presented with sudden left-sided weakness, difficulty swallowing, headaches, and speech difficulties. Examination revealed right cranial nerve paresis and decreased left extremity strength. MRI showed a pontine glioma. Surgery preparation included fasting, fluid calculation, and medication readiness. Anesthesia induction involved midazolam premedication, propofol induction, and remifentanil for intubation. Monitoring included EtCO2 and oxygen saturation maintenance. Intraoperatively, target-controlled infusion (TCI) propofol and compressed air sustained oxygenation. Paracetamol and tranexamic acid were administered. The surgery lasted five hours in the left lateral decubitus position. Postoperative analgesia included fentanyl and oral paracetamol. The patient spent seven days in the PICU on a ventilator before discharge on the eighth day. In summary, the case of the four-year-old girl with left-sided weakness and difficulty swallowing, diagnosed with pontine glioma, showcases the intricate multidisciplinary approach essential in pediatric neurosurgery.